2021
DOI: 10.1186/s40100-021-00198-0
|View full text |Cite
|
Sign up to set email alerts
|

Economics of contracts in African food systems: evidence from the malt barley sector in Ethiopia

Abstract: Foreign direct investment (FDI) facilitates modernization of domestic agri-food systems in emerging economies through increased use of vertical coordination. This paper sheds lights on how international brewer investments in African food systems affect smallholder market participation and value chain development. In particular, we analyze the impact of contracts among malt barley producers in Ethiopia. Using cross-sectional survey data, we employ inverse probability-weighted regression adjustment (IPWRA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…The result is similar to Weldeyohanis et al 13 who suggested that farmers are the main value chain actors in the malt barley production value chain and perform most of the primary functions by receiving inputs from input suppliers. Contracting of farmers with buyers has its own positive and significant implication on intensification, malt barley production, quality improvement and commercialization regarding increasing producersʼ income 17 . All malt barley producers in the study area were smallholder farmers having different land sizes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is similar to Weldeyohanis et al 13 who suggested that farmers are the main value chain actors in the malt barley production value chain and perform most of the primary functions by receiving inputs from input suppliers. Contracting of farmers with buyers has its own positive and significant implication on intensification, malt barley production, quality improvement and commercialization regarding increasing producersʼ income 17 . All malt barley producers in the study area were smallholder farmers having different land sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Improved malt barley seeds, fertilizer and pesticides are the major agricultural inputs that are commonly used by malt barley producers 17 .…”
Section: Gondar Agricultural Researchmentioning
confidence: 99%
“…The presence of POs in contract farming can be beneficial and can help to create more efficient VC mechanisms to comply with food quality and safety requirements (Moustier et al, 2010, Tefera and Bijman, 2021, Mwambi et al, 2020. As POs are organisations that are formed by farmers, their key function is to provide goods and services to their members (Bijman, 2016).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…In practice, however, CFAs and POs are often combined in agri-food chains, where contracts are often entered with the PO rather than with individual farmers. The PO acts as intermediary, providing coordination among farmers and between the farmers and the buyer (Fischer and Qaim, 2012, Jia and Huang, 2011, Mugwagwa et al, 2018, Tefera and Bijman, 2021. This thesis addresses this knowledge gap by analysing combinations of contracting and PO in value chains, particularly how these combinations link smallholders with modern retail markets, increase food quality, increase safety performance and build quality relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation